Nectariferous and melliferous properties of species in the genus Nepeta L. in forest-steppe zone of Ukraine and recommended procedure for determination of relevant indexes (CHORNOMORSKI BOTANICAL JOURNAL, 2010)
Recommended procedure are working out for determinating melliferous properties of species in the genus Nepeta L. Nectariferous and melliferous properties of Nepeta grandiflora M.Bieb., N. transcucasica Grossh., N. mussinii Spreng. ex Henckel that introduced in M. M. Grishko National Botanical Garden of the National Academic Sciences of Ukraine (forest-steppe of Ukraine) are determined for the first time. The results obtained evidence these species can be used as melliferous plants.
Keywords: Nepeta L., introduction, melliferous property, guideline.